CHANGES IN THE NUMBER OF MACROLEPIDOPTERA INDIVIDUALS AND SPECIES CAUGHT BY LIGHT-TRAP, IN CONNECTION WITH THE GEOMAGNETIC M-INDEX (Acta Entomologica Serbica, 2016)
The authors studied the number of Macrolepidoptera individuals and species caught by light-trap, in relationship with the geomagnetic M-index.A correlation was found between the averaged geomagnetic M-index values measured at night, and the number of individuals and species caught by light-trap in the Kámon Botanic Garden (Hungary).The authors studied the number of Macrolepidoptera individuals and species caught by light-trap, in relationship with the geomagnetic M-index.A correlation was found between the averaged geomagnetic M-index values measured at night, and the number of individuals and species caught by light-trap in the Kámon Botanic Garden (Hungary).